Regulatory T cell therapy for xenotransplantation, what perspectives? - Porret, Raphaël; Lana, Erica; Mancarella, Antonio; Guillaume, Philippe; Pascual, Manuel; Meier, Raphael P. H.; Bromberg, Jonathan S.; Mohiuddin, Muhammad M.; Buhler, Leo H.; Tang, Qizhi; Muller, Yannick D. (Frontiers in Immunology, 2025)
Xenotransplantation has experienced major clinical advancements over the past three years. Yet, despite potent immunosuppressive regimens combining B-cell depleting therapies, T cell activation blockade, complement inhibition, and high-dose steroids, signs of antibody-mediated and cellular rejection were seen in the few pig-to human heart and kidney xenotransplants. Considering the recent success of chimeric antigen receptor T cell therapies in severe refractory autoimmune diseases, there are windows for opportunities to develop novel approaches to reduce the burden of immunosuppression. In this line, regulatory T cell (Treg) therapy is an attractive strategy, as Tregs could be genetically modified to recognize pig organs. In this brief review, we summarize the lessons learned from Tregs therapies in allotransplantation, update on the recent development in Treg research for xenotransplantation, and discuss future perspectives of humanizing pigs with human leukocyte antigens to promote tolerance using engineered Tregs.